HUBUNGAN KELENGKAPAN REKAM MEDIS DAN FREKUENSI KONSELING KESEHATAN DENGAN TINGKAT KEPATUHAN PASIEN DIABETES MELLITUS DALAM PENGOBATAN - Yudhanto, Satrio Bhagas; Rahman, Khalilul; Wirman, Wirman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This study aims to analyze the impact of medical record completeness and frequency of health counseling on patient adherence to treatment. This quantitative research used a bivariate analysis approach to examine the relationship between two independent variables, namely medical record completeness and frequency of health counseling, with one dependent variable, patient adherence. The study sample consisted of 150 patients receiving treatment at a hospital in Padang City. The results show a significant effect of both medical record completeness and frequency of health counseling on patient adherence levels. Patients with complete medical records and those who received more frequent counseling showed higher adherence to the treatment regimen. This study provides valuable insights into the importance of medical record completeness and health counseling as key factors influencing patient adherence to treatment. These findings can serve as a basis for improving the quality of healthcare services in hospitals by addressing factors that influence patient adherence.Keywords: Medical Record Completeness, Health Counseling Frequency, Patient Adherence, Treatment, Hospital